The Post-Treatment Experience of Cancer Survivors with Pre-Existing Cardiopulmonary Disease - Becker, Heather (2010)
PURPOSE: The purpose of this study was to explore the cancer experience of survivors with pre-existing diagnoses of heart and/or lung disease following active treatment. METHOD: The Lance Armstrong Foundation recruited cancer survivors throughout the United States to complete a web-based survey to provide insight into post-treatment supportive care needs. Experts in survey methodology and oncology, as well as cancer survivors, provided input into the survey. RESULTS: The 137 individuals whose physicians told them they had heart or lung problems were 50 years old on average, and most were more than five years past active treatment. Two-thirds of these respondents reported pain for long periods, and 20% of them agreed that they now need help with everyday tasks that they did not need help with before their cancer. Among those who were tired, had no energy, or had trouble sleeping and/or resting, less than half (47%) agreed that they had received help with this problem. One third of these respondents indicated that they had decreased their physical activity since their cancer diagnosis because of fatigue and 26% decreased their activities because of pain. More respondents indicated that their needs were met during their cancer treatment than afterwards. CONCLUSIONS: Researchers and health care providers are urged to consider the unmet supportive care needs of cancer survivors with co-morbid conditions following active treatment, particularly the need for careful monitoring of their complex health conditions.